Industry-Based Learning Model in Vocational Schools - Yahya, Muhammad; Purnamawati; Komeini, Muhammad (Pascasarjana Universitas Negeri Makassar, 2023)
This study aims to find out: 1) assessment of the needs of WBL learning model development and 2) the effectiveness of the WBL model to improve electrical measurement skills. Data collection techniques through interview and questionnaire methods. The research approach is development research (R&D) with the concept of Thiagarajan 4D (Define, Design, Develop, and Disseminate). The data were analyzed with descriptive, qualitative and inferential statistics. This research is a qualitative descriptive research by analyzing the material needs for the development of learning models. The results of the study were in the form of WBL model learning products on TBU cadet electrical measurement practices that were feasible and effective: 1) the need for professional identity, aspects of personal knowledge in metacognitive competence contributed the most to the achievement of electrical measurement skills, and 2) test results in the TBU IX experimental class group with effective WBL model learning compared to the results o f the TBU X control class group through traditional learning.